Unruly Children: Blake's Book of Urizen and Embryology's Break from Newtonian Law. Issue 1 (April 2016) - Fletcher, Joseph
Abstract : William Blake's conflation of cosmology and embryology in the The Book of Urizen testifies to his view that Newtonian mechanism and empirical philosophy had infiltrated the new discoveries being made in the eighteenth-century life sciences. Ironically, however, emerging vital materialist physiologies and theories of embryological development, though voicing allegiance to the laws of Newton, ultimately revealed a living world that could not be contained in or explained by his metaphysical system – a state of affairs that I argue Blake dramatizes in Urizen, wherein the Newtonian Urizen despairs over his reptilian offspring, who cannot keep "his iron laws one moment." Despite their anti-Newtonian implications, the various vitalist natural philosophies were for Blake another form of natural religion, for they too denied divinity to the self-active living matter of the universe. Urizen 's dark satire thus attacks both Newtonian law and the materialist embryological theories that transgressed it.